Analysis of Investment Feasibility Study of Bandung Intra Urban Toll Road in Bandung City - Ghinaa Salsabila Putri; Juang Akbardin; Siti Nurasiyah (Portal: Jurnal Teknik Sipil, 2025)
This study aims to analyze the investment feasibility of the Bandung Intra Urban Toll Road (BIUTR) construction project using Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PP), and Benefit-Cost Ratio (BCR) methods. The research employs a quantitative descriptive approach, analyzing investment and operational costs projected over a 45-year concession period. Data were processed into project cash flows and evaluated using investment feasibility indicators. The results show that under the Rp1,600 tariff scenario, the project yields a positive NPV of Rp90.66 billion and an IRR of 11.04%, which exceeds the Minimum Attractive Rate of Return (MARR) of 9.31%. The payback period is reached in year 22, month 7, and day 14, indicating the project begins to generate net profit before the concession ends. A BCR value greater than 1 also indicates that the financial benefits outweigh the incurred costs. These findings are expected to serve as a reference for the government and investors in making strategic decisions regarding toll road infrastructure investments based on financial feasibility.